S91 The role of the vitamin D axis in lung cancer. (16th November 2010) - McGowan, L A; Wood, A M; Newby, P; Naidu, B
Abstract : Introduction: Vitamin D deficiency has been associated with many cancers, although little is known about its role in lung cancer. This is biologically plausible since vitamin D influences apoptosis and inhibits cell proliferation. Vitamin D receptor (VDR) polymorphisms have also been suggested to play a role in genetic susceptibility, their direction being consistent with inability to respond to vitamin D. Finally, vitamin D binding protein (DBP) indirectly activates alveolar macrophages, a higher number of which within a tumour links to better prognosis in lung cancer. Methods: 37 patients with a diagnosis of lung cancer were studied in the first phase, together with 18 healthy controls. Circulating vitamin D level was measured at initial presentation by tandem mass spectrometry, and DBP by ELISA. Vitamin D and DBP level was compared between groups, and against other clinical features. VDR was quantified in normal lung and tumour tissue by immunohistochemistry, and compared between the two. In the second phase the lung cancer patients were genotyped for four functional SNPs in the vitamin D pathway, and their genotype frequencies compared to 484 healthy controls. Results: Vitamin D levels were lower in lung cancer than controls, after adjustment for season of collection (21.8 vs 15.5 ng/ml, p=0.018), as was DBP (28.2 vs 51.7 mg/dl). DBP was higher in women (p=0.001) and correlated directly with vitamin D (r=0.446, p=0.013). VDR was expressed primarily in bronchial epithelium, and to a lesser extent in pneumocytes, but was generally expressed less in tumour tissue (Abstract S91 Figure 1 ). Of the four SNPs studied two were associated with lung cancer; the associated allele of rs4588 is known to reduce macrophage activation and conferred an odds ratio (OR) of 3.04, whilst that of rs1544410 produces less stable VDR mRNA and conferred an OR of 4.10 of disease. Conclusions: Vitamin D deficiency is common in lung cancer, but reduced VDR in tumour tissue suggests that it is unlikely to be useful as an adjuvant treatment, as tumour tissue will not be able to respond to it. We have also confirmed the role of VDR polymorphisms in lung cancer, similar to other malignancies.